Association between early childhood caries and malnutrition in a sub-urban population in Nigeria - Morenike Oluwatoyin Folayan; Olujide Arije; Maha El Tantawi; Kikelomo Adebanke Kolawole; Mary Obiyan; Olaniyi Arowolo; Elizabeth O. Oziegbe (BMC, 2019)
Abstract Background To determine the association between malnutrition and early childhood caries (ECC) in children resident in sub-urban, Nigeria. Methods This study was a subset of a larger cross-sectional study the data of which was generated through a household survey conducted in Ile-Ife, Nigeria. The study's explanatory variable was malnutrition (underweight, overweight, wasting and stunting) and the outcome variable was ECC. Poisson regression analysis was used to determine the association between ECC and malnutrition. Variables (sex, frequency of sugar consumption, maternal knowledge of oral hygiene, oral hygiene status) associated with ECC in the primary study were adjusted for to obtain the adjusted prevalence ratio (APR). Results Of the 370 children, 20 (5.41%) were underweight, 20 (5.41%) were overweight, 67 (18.11%) were wasting, 120 (32.43%) were stunted and 18 (4.86%) had ECC. Factors associated with ECC were being stunted, underweight, overweight and fair oral hygiene. The prevalence of ECC was lower in children who were stunted (APR: 0.14; 95% CI: 0.03-0.69; p = 0.02), almost seven times higher in children who were overweight (APR: 6.88; 95% CI: 1.83-25.85; p < 0.001), and predictively absent in children who were underweight (APR: 0; 95% CI: 0-0; p < 0.001) when compared with children who had normal weight. Non-significant risk indicators for ECC included consuming sugar between meals three times a day or more, having low socioeconomic status and being female. Conclusions For this study population, the indicators of malnutrition - being stunted, underweight, overweight - and fair oral hygiene were risk indicators for ECC. The frequency of sugar consumption was not a significant risk indicator when malnutrition was included as an explanatory variable for ECC in the study population.